Media social sebagai alat strategi komunikasi politik untuk mendapatkan dukungan massa: Studi Kasus Akun Tiwtter anise baswedan - Nur Aisyah, Ayu; Sakir, Sakir; Sutan, Arissy Jorgi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
The power of social media to influence society is based exclusively on its social aspect: this means the interaction and participation that can be achieved through campaigns. Campaigns are basically the delivery of messages from the sender to the audience. The aim of this research is to explain the use of social media to gain mass/public support specifically for Anies Baswedan in the scope of social media Twitter. The research is qualitative, the type of data is secondary, explained about Twitter and Litelatue. Data collection technique; literature studies, data analysis techniques; descriptive analysis technique - depicting/describing results/phenomena. Through social media, political messages are faster and easier to be received by the public and information can be accessed easily. We will examine further how Anies utilizes the social media Twitter so that he can gain mass support through political communication using the social media Twitter.